In Vitro Effects of Cryptotanshinone on Early Atherogenic Events Induced by Oxidized Low Density Lipoprotein and Tumour Necrosis Factor-α - Ang, Kok Pian (2010)
Development of early atherogenic events involve endothelial cell injury by oxidized low-density lipoprotein (oxLDL) and pro-inflammatory cytokines, such as tumour necrosis factor-α (TNF-α). The injuries of endothelial cells lead to subsequent increase in endothelial permeability and expression of adhesion molecules favouring monocytes’ adhesion to endothelium. In addition, the production of nitric oxide (NO), a permeability-regulator, is also impaired in dysfunctioned endothelium. Cryptotanshinone (CTS) is one of the major compounds isolated from the Chinese herb Salvia milthiorrhiza, which is found to be effective against cardiovascular diseases. However, the effects of CTS on oxLDL and TNF-α-induced early atherosclerotic events have not been investigated. The aim of this study was to evaluate the anti-atherosclerotic effects of CTS at pre-lesional stage by examining its effects on the endothelial permeability, expression of adhesion molecules and chemokines, restoration of nitric oxide (NO) and adhesion of U937 monocytic cells to human umbilical vein endothelial cells (HUVEC). OxLDL (100 μg/ml) and TNF-α (10 ng/ml) were used to induce endothelial hyperpermeability, to increase expression of adhesion molecules, i.e. vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecules-1 (ICAM-1), adhesion of monocytes, and to suppress NO. TNF-α was also used to induce the expression of monocyte chemoattractant protein-1 (MCP-1) in HUVEC. The results of MTT assay showed that CTS had no cytotoxic effect to HUVEC up to 10 μM concentration. During oxLDL-induced early atherogenic events, CTS, at 1-10 μM, significantly suppressed the endothelial hyperpermeability and at 2.5 - 20 μM, it significantly reduced the adhesion of monocytes to HUVEC and restored the production of NO. ICAM-1 was significantly suppressed by 2.5 – 10 μM of CTS whereas VCAM-1 expression was suppressed by 1 – 20 μM of CTS. For the events induced by TNF-α, 1 – 20 μM CTS significantly reduced endothelial hyperpermeability, 1 – 10 μM CTS significantly suppressed monocytes’ adhesion to HUVEC, the expression of ICAM-1, and at similar range of concentrations, restored NO production CTS, at 2.5 – 10 μM, significantly suppressed the expressions of VCAM-1 and MCP-1 (P<0.05). These findings suggest that CTS may play a role in the prevention of early or pre-lesional stage of atherosclerosis by suppressing increased endothelial permeability and monocytes’ adhesion to endothelium. These data indicate that the restoration of NO bioavailability may play a role in reversing the elevated endothelial permeability, and that CTS may attenuate the recruitment of monocytes via the suppression of adhesion molecules and chemokine’s expressions.